Sleep Disorders in Children - Nevšímalová, Soňa; Bruni, Oliviero (Springer International Publishing : Imprint: Springer, 2017)
This book is both an exam guide to children´s sleep medicine and a practical manual for diagnosis and management of sleep disorders in children. An overview of the most frequent sleep disorders encountered in newborns, infants, children and adolescents is provided. This book discusses the main sleep disorders in detail, including insomnia, respiratory disturbances, movement disorders during sleep, circadian rhythm disorders, parasomnias, and disorders associated with increased sleepiness. It also covers sleep disorders associated with neurological, psychiatric, and medical diseases. This book is divided into two parts. The first part is an introduction to childhood sleep physiology and pathology, epidemiology of sleep disorders, and diagnostic procedures. The second part describes the most frequent sleep disorders in greater depth. Sleep Disorders in Children is aimed at sleep researchers, pediatricians, child neurologists and child psychiatrists, as well as patient organizations and families with affected children.
Keywords: Medicine.; Respiratory organs -- Diseases.; Neurology.; Pediatrics.; Psychiatry.; elektronické knihy; electronic books